Global Political Leadership In Search of Synergy - Zachara-Szymańska, Małgorzata (Rethinking Globalizations, 2023)
Global Political Leadership explores contemporary shifts in leadership, and the related leadership crisis, in the global world. Globalization is now perceived as a threatening and hostile force, with many of its advocates and political supporters turning away from it, but its processes cannot be reversed. New powers emerge, old ones re-emerge, and uncertainty about the future global order is increasing. This book tells the inside stories of global power games and asks important questions about the leadership crisis in the western world. The author provides an interpretative framework for contemporary shifts within the western political sphere based on the concept of global leadership. This framework presents the nature of the transformation caused by global processes, as part of which force and coercion have ceased to be the main modus operandi of the international realm. The issue of global political leadership has often been neglected in international relations literature, while being widely exploited by managerial and organizational studies. However, all social organizations have 'gone global' within the last several decades; they are more interconnected and more dependent on global processes, so the question of effective leadership strategies matching these new realities is highly necessary, even - or especially - at a time when globalization is no longer seen as a leading political programme. This book will be of great interest to students and scholars of global affairs, politics and international relations, leadership and development, and diplomatic studies.